RELATED PARTIES’ TRANSACTION AND EARNINGS MANAGEMENT: A CASE IN INDONESIA - Sumiyana Sumiyana; Rahmat Febrianto (Journal of Indonesian Economy and Business (JIEB), 2012)
This study investigates the association between related parties’ transactions and earnings management in Indonesia. Firm's executives officers accompanied by board of director members usually engage in related parties’ transactions to expropriate the firm’s resources. Therefore, they have incentives to manage earnings either to increase theirperquisites or possibly to mask such expropriation.This study presents evidence that earnings management is positively associated with certain types of related parties’ transactions. Overall, this study concludes that concernsabout related parties’ transactions as a factor associated with earnings management are warranted, especially for certain related parties’ transactions. There are purchase costs from subsidiary or parent companies and expenses incurred from the firm’s related parties’ transactions.Keywords: related parties’ transactions, perquisite, earnings management.